2005
DOI: 10.1074/jbc.m504583200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-induced Rapid Retinoblastoma Phosphorylation at Ser780 and Ser795 Is Mediated by ERK1/2 in Small Intestine Epithelial Cells

Abstract: The retinoblastoma protein Rb is critical for the regulation of mammalian cell cycle entry. Hypophosphorylated Rb is considered to be the active form and directs G 1 arrest, while hyperphosphorylated Rb permits the transition from G 1 to S phase for cell proliferation. Upon stimulation by various growth factors, Rb appears to be phosphorylated by a cascade of phosphorylation events mediated mainly by kinases associated with cyclins D and E. Here we report that in prototype small intestine crypt stem cells (RIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Hyperphosphorylation at serine 780, serine 807/ 811, and threonine 821/826 appears to be involved in the disruption of E2F binding to Rb [16]. Therefore, the phospho-Rb-positive cells in our study may not be capable of binding to E2F.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Hyperphosphorylation at serine 780, serine 807/ 811, and threonine 821/826 appears to be involved in the disruption of E2F binding to Rb [16]. Therefore, the phospho-Rb-positive cells in our study may not be capable of binding to E2F.…”
Section: Discussionmentioning
confidence: 46%
“…The significance of Rb phosphorylation at different sites is suggested by the observation that Rb function may be modulated according to the location at which it is phosphorylated [16]. Hyperphosphorylation at serine 780, serine 807/ 811, and threonine 821/826 appears to be involved in the disruption of E2F binding to Rb [16].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Guo et al (2005) demonstrated that in prototype small intestine crypt stem cells the activity of RB is regulated at multiple levels. The acute loss of intestinal regions triggers mitogenic signals to the intestinal crypt cells to grow taller villi and deepen the crypts in order to increase the area of remaining absorptive and digestive mucosa.…”
Section: Small Intestine Crypt Stem Cellsmentioning
confidence: 99%
“…The acute loss of intestinal regions triggers mitogenic signals to the intestinal crypt cells to grow taller villi and deepen the crypts in order to increase the area of remaining absorptive and digestive mucosa. Among the different mitogens, the EGF-mediated signaling appears to play a major role in this process (Guo et al, 2005). The treatment of RIEC-6 cell cultures (a model of small intestine crypt stem cells) with EGF induces a sustained proliferation that is associated with a heavy pRb phosphorylation.…”
Section: Small Intestine Crypt Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation